1970
DOI: 10.1017/s0022029900013339
|View full text |Cite
|
Sign up to set email alerts
|

Milk enzymes—their distribution and activity

Abstract: SummaryThe distribution and activity of alkaline phosphatase (E.C. 3.1.3.1), acid phosphatase (E.C. 3.1.3.2), catalase (E.C. 1.11.1.6), xanthine oxidase (E.C. 1.2.3.2), aldolase (E.C. 4.1.2.7 and 4.1.2.13), ribonuclease (E.C. 2.7.7.16) and carbonic anhydrase (E.C. 4.2.1.1) were studied in the major components of bovine milk. Fractionation was accomplished by centrifugation of milk, skim-milk and buttermilk, and ammonium sulphate precipitation of skim-milk serum. The range of activities found for the enzymes st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
2
1

Year Published

1986
1986
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 20 publications
3
28
2
1
Order By: Relevance
“…The term 'spilling over' from epithelial mammary cells or serum during milk secretion was used in earlier (Kitchen, Taylor, & White, 1970) and later (Farkye, 2003) studies as an explanation for their presence in milk. However, it is doubtful if the term 'spill over' is justified in explaining the origin of enzymes in milk.…”
Section: Distribution Of Milk Enzymesmentioning
confidence: 99%
“…The term 'spilling over' from epithelial mammary cells or serum during milk secretion was used in earlier (Kitchen, Taylor, & White, 1970) and later (Farkye, 2003) studies as an explanation for their presence in milk. However, it is doubtful if the term 'spill over' is justified in explaining the origin of enzymes in milk.…”
Section: Distribution Of Milk Enzymesmentioning
confidence: 99%
“…Plasmin is heat stable with large percentages surviving minimum pasteurization (72°C for15 sec) (Politis et al, 1989). Even after UHT treatment, 30 to 40% of plasmin activity can still remain (Kitchen et al, 1970). Other researchers have indicated that extensive proteolysis in milk can result in the accumulation of small in milk can result in the accumulation of small hydrophobic peptides, causing bitterness and astringency.…”
Section: Effect Of Somatic Cell On Pasteurized Milkmentioning
confidence: 99%
“…If the somatic cell count exceeds 500,000/ml, it is considered indicative of mastitis (2,32). It is recognized that other factors can affect somatic cell counts, such as the individual cow, the stage of their lactation, the age of the cow, and the mastitis hist~ry of the individual cow (32), also increased somat ic cell counts in response to udder trauma such as stepped-on teat in the absence of infectious agents, can give misleading results about microbial infections (22) . In normal milk, somatic cells consist of 80% epithelial cells and nine percent neutrophils.…”
Section: Somatic Cellsmentioning
confidence: 99%
“…If milk from a normal , healthy cow was tested for enzymatic activity , it would show the presence of a number of enzymes which are believed to be derived from the secretory epithelial cells of the mammary gland . Their presence may be regarded as a "spilling over" from cells and serum during the milk secretion process (22). This results in an increased number of neutrophils in milk , since they have lipase, phospholipase, and proteinase enzymes which are active in destroying bacteria .…”
Section: Somatic Cellsmentioning
confidence: 99%
See 1 more Smart Citation